Criterion-Referenced Assessment for Strengthening Critical Thinking in Islamic Education - Mutia Rahmawati; Dina Hermina (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines the role of criterion-referenced assessment in strengthening critical thinking skills in Islamic Education. The study is motivated by the dominance of memorization-oriented assessment practices that limit students’ analytical and reflective abilities. Previous studies have discussed authentic assessment and higher-order thinking skills, yet limited attention has been given to criterion-referenced assessment as a framework for developing critical thinking in Islamic Education. This research employed a qualitative approach using library research methods. Data were collected from books, journal articles, and academic publications issued within the last ten years and analyzed through content analysis. The findings indicate that criterion-referenced assessment supports critical thinking development through competency-based evaluation, analytical learning tasks, reflective learning processes, and measurable learning indicators. The analysis further reveals that students’ critical thinking is strengthened when assessment emphasizes mastery of learning criteria, evidence-based reasoning, and continuous feedback rather than comparison with peers. Furthermore, this assessment approach encourages a shift from score-oriented evaluation toward competency and reasoning-based assessment in Islamic Education. The study concludes that criterion-referenced assessment provides an innovative framework for strengthening critical thinking and supporting 21st-century learning competencies.